Association of Depression With Functional Mobility in Schizophrenia - Kim, Jiheon; Shin, Ji-Hyeon; Ryu, Jeh-Kwang; Jung, Jae Hoon; Kim, Chan-Hyung; Lee, Hwa-Bock; Kim, Do Hoon; Lee, Sang-Kyu; Roh, Daeyoung (Frontiers in Psychiatry, 2020)
Background: Functional immobility can cause functional disability in patients with schizophrenia and has been linked to prognosis and mortality. Although depression might be a barrier for physical activity engagement, scarce data are present on the relationship between depression and functional mobility (FM) in schizophrenia. Thus, we aimed to investigate the associations among FM, depression, and other clinical correlates in individuals with schizophrenia. Methods: FM was evaluated by the pedometer-assessed daily steps and Timed Up-and-Go (TUG) test in the daily-living and clinical settings, respectively. Psychiatric symptoms were assessed using the Beck Depression Inventory, Brief Psychiatric Rating Scale (BPRS), and State-Trait Anxiety Inventory. Cognitive function was evaluated using the Sternberg Working Memory (SWM) Task. Multiple regression analyses were performed to identify predictive factors associated with FM, with adjustment for relevant covariates. Results: Sixty patients were enrolled in this study. Depression was the most consistent explanatory variable for both pedometer (β = -0.34, p = 0.011) and TUG time (β = 0.32, p = 0.018). Additionally, SWM accuracy (β = -0.29, p = 0.018), BPRS-Withdrawal (β = 0.19, p = 0.139), and fasting blood sugar (β = 0.34, p = 0.008) were associated with TUG time. However, psychotic symptoms and anxiety were not associated with pedometer and TUG. Conclusions: We identified an association between depression and FM after adjusting for other disorder-related correlates in schizophrenia. Since the intervention goal is functional recovery, improving FM by treating depression may have considerable therapeutic value.